Characterization of the Oligomerization and Aggregation of Human Serum Amyloid A - Patke, Sanket (Public Library of Science, 2013)
The fibrillation of Serum Amyloid A (SAA) – a major acute phase protein – is believed to play a role in the disease Amyloid A (AA) Amyloidosis. To better understand the amyloid formation pathway of SAA, we characterized the oligomerization, misfolding, and aggregation of a disease-associated isoform of human SAA – human SAA1.1 (hSAA1.1) – using techniques ranging from circular dichroism spectroscopy to atomic force microscopy, fluorescence spectroscopy, immunoblot studies, solubility measurements, and seeding experiments. We found that hSAA1.1 formed alpha helix-rich, marginally stable oligomers in vitro on refolding and cross-beta-rich aggregates following incubation at 37°C. Strikingly, while hSAA1.1 was not highly amyloidogenic in vitro, the addition of a single N-terminal methionine residue significantly enhanced the fibrillation propensity of hSAA1.1 and modulated its fibrillation pathway. A deeper understanding of the oligomerization and fibrillation pathway of hSAA1.1 may help elucidate its pathological role.